The development and validation of the 'Good Life in the Community Scale' (GLiCS): a validation study with women migrants living in high income countries - C. F. Van der Boor; P. Christiansen; P. Anand; R. White (BMC, 2022)
Abstract Background To date, few assessment instruments have been developed to quantitatively measure the mental health status of migrant populations specifically. This paper describes the development and preliminary assessment of the 'Good Life in the Community Scale' (GLiCS). GLiCS is a wellbeing measure for migrant women in high-income settings that was coproduced with experts by experience across two phases. Methods The study used a mixed-methods approach and was composed of two phases. Phase I: 88 initial items generated using qualitative data collected in a previous study were reduced to 42 through consultation with expert advisory panels, based on whether each item was considered understandable and relevant Phase II: these 42 items were piloted with a sample of migrant women (N = 109). A preliminary exploratory factor analysis was conducted using Oblique rotation. Internal consistency was measured using McDonald's ω. Convergent validity was tested by correlating the GLiCS with the Oxford Capabilities Questionnaire Mental Health (OxCAP-MH), WHO-5 wellbeing index and Objective Social Outcomes Index (SIX). Incremental validity was tested using hierarchical regression analysis to ascertain the effect on the WHO-5 wellbeing index of: age, migration status, SIX, OxCAP-MH and GLiCS. Known groups validity, the ability a measure has to discriminate between groups likely to differ on the variables of interest, was tested between the different migrant categories using a simple between subjects ANOVA. Results Exploratory factor analysis confirmed a 17-item (three-factor: (i) access to resources, (ii) belonging and contributing, (iii) independence) scale with high internal consistency (McDonald's ω = 0.91). Convergent and incremental validity were also evidenced. Conclusion The GLiCS has demonstrable good internal consistency and construct validity, and it presents a promising wellbeing measure for better understanding the experience of migrant women.